E-Test: Alternative Online Assessment for Online Learning Classes in Vocational High Schools - Sri Rahayu; Friyatmi Friyatmi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to develop a moodle – based online test to asses the student learning outcome in vocational high school. It is expected to help and facilitate the teacher in correcting out the evaluation of learning at school. This study was research and development which in included 4 stages : define, design, develop and disseminate. The subjeck of this research is accounting and instititional finance majoring students at grade XI. The results of the research  the Moodle-based online test which was developed based on the results of validation by IT experts obtained a score of 5 with the criteria of 'Very Good' for the display aspect and for the programming aspect. Meanwhile, for the practicality test, the application obtained a score of 88% which was in the range of 81%-100%.  So it can be concluded that the Moodle online test application which was developed  is "Very Good" so that,  it can be used to carry out the learning evaluation activities